Los cuerpos mártires. Subjetividad, sexualidad y revolución en el beso de la mujer araña de Manuel Puig - Peller, Mariela (Nómadas. Critical Journal of Social and Juridical Science, 2009)
el beso de la mujer araña of Manuel Puig was published by the first time in Spain in 1976, during the last military Argentine dictatorship. The novel treats on the dialogs between two prisoners: one homosexual and one militant of the left side. In this article there are analyzed the discussions that, personified in the dialog among these two characters, are established between the left side and the homosexual movement, in the seventies. The analysis of this dialog supposes a reflection on the constitution of sexual and political identities that develop in the novel. This essay holds that the novel discuss the sexual and political identities, by means of the utilization of dichotomies (desire/politics, body/mind, practice/theory, feminine/ masculine) as way of putting in evidence contradictions and displacements in the binary logic.
Keywords: Subjectivity; Sexuality; Politics; Manuel Puig